Angiopep-2 conjugated nanoparticles loaded with doxorubicin for the treatment of primary central nervous system lymphoma. (3rd January 2020) - Shi, Xiao-Xiao; Miao, Wei-Min; Pang, Di-Wen; Wu, Jia-Si; Tong, Qi-Song; Li, Jia-Xian; Luo, Jia-Qi; Li, Wen-Yu; Du, Jin-Zhi; Wang, Jun
Abstract : APP nanoparticle was developed to deliver DOX for the treatment of PCNSL. The results indicated that APP@DOX could overcome the BBB, and significantly prolong the survival time of mice with an intracranial SU-DHL-2 lymphoma xenograft. Abstract : Primary central nervous system lymphoma (PCNSL) is a rare brain tumor. Its therapeutic efficacy is much lower than that of traditional lymphoma, largely due to the presence of the blood–brain barrier (BBB), which hinders the effective drug delivery and deposition on the disease site. Angiopep-2 (ANG) can target low-density lipoprotein receptor-related protein (LRP) on the surface of brain capillary endothelial cells (BCECs) and exhibits high BBB transport capability. In this study, we designed an ANG conjugated poly(ethylene glycol)- b -poly(ε-caprolactone) (PEG- b -PCL) (APP) nanoparticle to deliver doxorubicin (DOX) for the treatment of PCNSL. Our data indicated that the targeted APP nanoparticles showed significantly increased cellular uptake by BCECs compared with the control nanoparticles. In the intracranial SU-DHL-2-LUC lymphoma xenograft mice model, APP enhanced drug deposition in tumor tissues, and DOX-loaded APP (APP@DOX) exhibited a better therapeutic effect than free DOX and nontargeted PP@DOX, which significantly prolonged the survival time of mice.